Prognostic significance of preoperative neutrophil-to-lymphocyte ratio in lung carcinoid patients after receiving curative surgery. A multicentre study - Nicola Tamburini; Beatrice Aramini; Ilaria Potenza; Francesco Bagolini; Danila Azzolina; Fares Shamshoum; Federico Rea; Franco Stella; Giampiero Dolci; Enrica Pellizzer; Pio Maniscalco; Andrea Dell’Amore (Frontiers in Oncology)
BackgroundRecent evidence suggests that inflammation is relevant to carcinogenesis and tumor progression. Biomarkers of the inflammatory response are increasingly regarded as valuable prognostic indicators for enhancing predictive accuracy in non-small cell lung cancer (NSCLC). Nonetheless, the applicability of these measures in patients with pulmonary carcinoid remains uncertain.ObjectivesThe primary outcome of this study was to evaluate the prognostic impact on Overall Survival (OS) of the preoperative neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and serum C-reactive protein (CRP) in pulmonary carcinoid after complete surgical resection.MethodsWe retrospectively evaluated data from 267 patients who underwent surgery with curative intent for pulmonary carcinoid tumors between January 2010 and December 2020. Peripheral blood samples were collected preoperatively during routine preoperative tests. The univariable-unadjusted and the Inverse of Probability Weight (IPW) propensity score (PS) adjusted Cox regression models are reported to assess the association between inflammatory biomarkers and outcomes.ResultsThe median follow-up duration after surgical resection was four years. Elevated NLR was the only biomarker significantly associated with worse overall survival (OS). The significant association between NLR and OS is evidenced after adjusting for potential confounders using IPW.ConclusionsThis study demonstrated a significant association between the NLR in blood samples of carcinoid patients and their survival outcomes.